Conservation of Penaeid Shrimp Resources with Special Reference to India - P.A., Panicker (Fishery Technology, 2025)
Penaeid shrimp esources world-wide are subject to high intensity of fishing pressure and exploited at levels very close to or exceeding optimum sustainable limits. Coastal penaeid shrimps in the tropics are characterised by fast growth rate, short life span and their availability to fisheries is estimated at a little over one year. This paper discusses several aspects of conservation of shrimp isheries with special reference to India. Shrimp sanctuaries, protection ofnatural habitats, seasonal closures, mesh regulation, ban on export of under-sized shrimps, and control of fishing effort have been considered as mefins of controlling growth overfishing and improving shrimp production in India. Adoption of selective trawling techniques is recommended for reducing juvenile finfish mortality.